A Smart Integrated Vest for the Canine Companion of the K9 Units - Georgios Vosinakis; Maria Krommyda; Angelos Stamou; Nikos Mitro; Marios Palazis-Aslanidis; Katerina Voulgary; Spyros Athanasiadis; Angelos Amditis (Informatics, 2021)
Search and rescue operations can range from small, confined spaces, such as collapsed buildings, to large area searches during missing person operations. K9 units are tasked with intervening in such emergencies and assist in the optimal way to ensure a successful outcome for the mission. They are required to operate in unknown situations were the lives of the K9 handler and the canine companion are threatened as they operate with limited situational awareness. Within the context of the INGENIOUS project, we developed a K9 vest for the canine companion of the unit, aiming to increase the unit’s safety while operating in the field, assist the K9 handler in better monitoring the location and the environment of the K9 and increase the information provided to the Command and Control Center during the operation.